2020
DOI: 10.18632/aging.103900
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of p62(SQSTM1)-engineered lactic acid bacteria in Alzheimer’s disease: a pre-clinical study

Abstract: Alzheimer's disease (AD) is a progressive neurodegeneration characterized by neuron death ending in memory and cognitive decline. A major concern in AD research is the identification of new therapeutics that could prevent or delay the onset of the disorder, with current treatments being effective only in reducing symptoms. In this perspective, the use of engineered probiotics as therapeutic tools for the delivery of molecules to eukaryotic cells is finding application in several disorders. This work introduces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 79 publications
2
31
0
Order By: Relevance
“…The disparity of different p62 protein levels in AD may reflect a different number of NFTs in the frontal and temporal cortices, given that NFTs are present in the temporal cortex earlier compared to the frontal cortex in AD according to Braak NFTs stages ( Braak et al, 2006 ). This study is consistent with previous findings that p62 was absent in neuritic plaques ( Kuusisto et al, 2002 ) and increased p62 exerted neuroprotective effects and reduced the number of senile plaques ( Cecarini et al, 2020 ; Deng et al, 2020 ). The p62 accumulation in NFTs might reduce cytosolic availability of p62 and decrease its physiological function in autophagy ( Feng et al, 2020 ), cellular signaling ( Gureev et al, 2020 ), and protein trafficking ( Ramesh Babu et al, 2008 ; Salminen et al, 2012 ).…”
Section: Discussionsupporting
confidence: 93%
“…The disparity of different p62 protein levels in AD may reflect a different number of NFTs in the frontal and temporal cortices, given that NFTs are present in the temporal cortex earlier compared to the frontal cortex in AD according to Braak NFTs stages ( Braak et al, 2006 ). This study is consistent with previous findings that p62 was absent in neuritic plaques ( Kuusisto et al, 2002 ) and increased p62 exerted neuroprotective effects and reduced the number of senile plaques ( Cecarini et al, 2020 ; Deng et al, 2020 ). The p62 accumulation in NFTs might reduce cytosolic availability of p62 and decrease its physiological function in autophagy ( Feng et al, 2020 ), cellular signaling ( Gureev et al, 2020 ), and protein trafficking ( Ramesh Babu et al, 2008 ; Salminen et al, 2012 ).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, they increase the integrity of the barrier and mucus production by exerting a trophic effect on intestinal mucosa and effects on epithelial cell cytokine secretion [ 33 , 133 ]. Oral bacteriotherapy with probiotics has been recently identified to treat and prevent many pathologies [ 134 , 135 ]. A systematic review suggested that preliminary animal studies support the potential role of probiotics in improving cognitive functioning, possibly by decreasing the levels of oxidative and inflammatory biomarkers in MCI or AD; Lactobacillus and Bifidobacterium strains could be the most promising candidates ( Table 4 ).…”
Section: Potential Therapeutic Strategies For Admentioning
confidence: 99%
“…p62 could be used a potential prognostic biomarker and therapeutic target for bone metastasis of lung adenocarcinoma. New promising research investigating a p62 vaccine treatment received good response in advanced solid tumors (30,31) and neurodegenerative disease (32). We propose that this new therapeutic strategy may improve clinical treatment of bone metastasis of lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 95%